Tebasan Penawa Sangga On Piodalan In Pura Luhur Pucak Padang Dawa Baturiti (Hindu Aesthetic Perspective) - Ni Luh Gede Mega Yanti; I Nengah Lestawi; Ida Bagus Gede Candrawan (Jayapangus Press, 2019)
The implementation of yajña or rituals requires of various means called upakara, in the form of offerings (banten). Banten which is made as a symbol of God's manifestation (Bhatara) contains aesthetic elements, devotion, obedience, and sincerity. The Hindu community in Bali believes that by using upakara means they get closer to God and its manifestations being adored. Means of upakara include: daksina, peras, sesayut, tebasan, suci and other ayaban. One of the tebasan was named tebasan penawa sangga. Tebasan penawa sangga was dedicated to the piodalan in Pura Luhur Pucak Padang Dawa which contains a religious aesthetic element. Tebasan penawa sangga educated the public so that the public will learn about the meaning, meaning and function used in the implementation of piodalan in Pura Luhur Pucak Padang Dawa. The theory used in this research were: (1) Religious theory, (2) Aesthetic theory, and (3) symbol theory. Sources of data used were primary data and secondary data. The method used to collect data was observation, interview, literature study, and document study. The data which had been collected were analyzed by using descriptive technique. The result of the research showed the aesthetic forms of the tebasan penawa sangga were: (1) the aesthetic form satyam, (2) the aesthetic shape siwam, (3) the aesthetic form sundaram. The functions of tebasan penawa sangga were: (1) The function of religious aesthetics, (2) The function of social aesthetics. The meanings of tebasan penawa sangga were: (1) the meaning of religious aesthetics, (2) the meaning of social aesthetics, 3) the meaning of aesthetics in education. As a final word, it was suggested to the leaders, figures of Hinduism and academics to provide guidance with the guidance and enlightenment regarding to the meaning of tebasan penawa sangga.